THE LEGAL CONSEQUENCES OF INCOMPLETE BUILDING LICENSE TO THE SALES AND PURCHASE AGREEMENT OF APARTMENTS (CASE STUDY OF MEIKARTA’S INCOMPLETE BUILDING LICENSE) - Sujana Donandi S (JURNAL PROFIT, 2017)
The construction of Meikarta, a place which is claimed as The New Jakartaon an Approximately 500 acres (ha) land has attracted public attention.There have been 117.797 reservation for apartments unit of Meikarta.However, the rejection from the government due to the incomplete buildinglicense of Meikarta has caused 2 main problems regarding the validity of theagreement of the apartment and its legal consequences caused by theincomplete building license. The purpose of this research are to examine thelegal validity of sales and purchase agreement of apartment which itsconstructing license is incomplete and To determine and describe the legalconsequences of it. This research will be conducted using normative legalresearch method. Normative Legal Research Method is a legal researchconducted by examining literacy sources or secondary sources.An Agreementof an apartment like Meikarta which its building license incomplete is nulland void.The status of an agreement that is null and void brings legalconsequences for each parties to restore themselves to the previous positionbefore the agreement was conducted, so that each parties should return backright of other party and vice versa.